Whole‐genome sequencing holds the key to the success of gene‐targeted therapies. Issue 1 (1st December 2022) - Vockley, Jerry; Aartsma‐Rus, Annemieke; Cohen, Jennifer L.; Cowsert, Lex M.; Howell, R. Rodney; Yu, Timothy W.; Wasserstein, Melissa P.; Defay, Thomas
Abstract: Rare genetic disorders affect as many as 3%–5% of all babies born. Approximately 10, 000 such disorders have been identified or hypothesized to exist. Treatment is supportive except in a limited number of instances where specific therapies exist. Development of new therapies has been hampered by at least two major factors: difficulty in diagnosing diseases early enough to enable treatment before irreversible damage occurs, and the high cost of developing new drugs and getting them approved by regulatory agencies. Whole‐genome sequencing (WGS) techniques have become exponentially less expensive and more rapid since the beginning of the human genome project, such that return of clinical data can now be achieved in days rather than years and at a cost that is comparable to other less expansive genetic testing. Thus, it is likely that WGS will ultimately become a mainstream, first‐tier NBS technique at least for those disorders without appropriate high‐throughput functional tests. However, there are likely to be several steps in the evolution to this end. The clinical implications of these advances are profound but highlight the bottlenecks in drug development that still limit transition to treatments. This article summarizes discussions arising from a recent National Institute of Health conference on nucleic acid therapy, with a focus on the impact of WGS in the identification of diagnosis and treatment of rare genetic disorders. Abstract : The diagnostic odyssey for rare diseases begins with the development of symptoms, but often requires significant time and financial expenses before a diagnosis is ultimately made. Use of genomic technology, originally whole‐exome sequencing, but increasing whole‐genome sequencing shortcuts this odyssey by introducing comprehensive genetic analysis into clinical practice early in the evaluation of an individual without a clear diagnosis after an abbreviated clinical assessment.